Methanation of simulated natural gas using alumina supported managanese doped ruthenium and palladium oxide catalyst [electronic resource] - Hazwan Faiz Abd. Rahim, 1987- (2012)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2012